OnePlus : crossing the chasm in the smartphone market - Sawhney, Mohanbir S.; Goodman, Pallavi (London : Kellogg School of Management, 2016)
In early 2016, after the success of its first two smartphones, the OnePlus One and OnePlus 2, China-based startup smartphone maker OnePlus was deciding how to build on its early success and grow into a global contender in the highly competitive smartphone market. Technology enthusiasts and geeks had flocked to purchase the first two generations of its smartphones and expectations were high for the company's next product. The company's founders, Pete Lau and Carl Pei, faced the challenge of broadening the appeal of OnePlus to address the mainstream market without alienating its core customer base."Crossing the chasm" from the early adopters to the mainstream market involved addressing three interrelated questions: First, what segments should OnePlus target as it sought to grow beyond its loyal fan base? Second, what value proposition and positioning strategy should it adopt to appeal to these target customers? Finally, what distribution and marketing communications strategy should it employ to make best use of its limited financial resources? A key consideration in formulating its strategy was to stay true to the company's culture and mission of "Never Settle" by charting its own course and not emulating the strategies of much larger competitors like Apple, Samsung, LG, and HTC.
Originally published in Sawhney, M., & Goodman, P. (2016). OnePlus: Crossing the chasm in the smartphone market. 5-216-253. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Lau, Pete; Pei, Carl; OnePlus -- Case studies; Smartphones -- China -- Case studies